Early- and Long-Term Outcomes After Surgery for Acute Type A Aortic Dissection in Patients Aged 45 Years and Younger - Ino, Takashi; Kawahito, Koji; Kimura, Naoyuki; Itoh, Satoshi; Okamura, Homare; Adachi, Hideo; Tanaka, Masashi; Yamaguchi, Atsushi (Circulation Journal, 2011)
Background: Acute type A aortic dissection (AAAD) is rare in young people. The early- and long-term outcomes after surgery for AAAD in patients aged ≤45 years was investigated. Methods and Results: Subjects were 355 patients who had undergone emergency surgery for AAAD. The patients were grouped as those aged ≤45 years (n=30; mean age, 38.3 years; younger group) and those aged >45 years (n=325; mean age, 65.3 years; older group). Clinical and prognostic variables were compared between the groups. Male sex, Marfan syndrome, and severe aortic regurgitation were more prevalent in the younger group. In-hospital mortality (16.7% vs. 8.6%, P=0.15) and postoperative patency of the distal aorta (90.8% vs. 59.1%, P<0.01) were more frequent in the younger group. The leading causes of late death were aortic rupture in the younger group (75.0%) and malignancy in the older group (27.5%). Although actuarial survival at 10 years was similar (64.5% vs. 62.5%), freedom from aortic reoperation at 10 years was decreased in the younger group (49.4% vs. 85.0%, P=0.012). A distal aorta >45mm (P<0.001), Marfan syndrome (P<0.01), and age ≤45 years (P=0.045) were shown to be independent risk factors for reoperation. Conclusions: Early- and long-term surgical outcomes are not better for patients ≤45 years, and the risk for reoperation is high in this group. Careful follow up is important in young patients with AAAD. (Circ J 2011; 75: 2135-2143)